Genome composition and taxonomic revision of Elymus purpuraristatus and Roegneria calcicola (Poaceae: Triticeae) based on cytogenetic and phylogenetic analyses. (5th February 2021) - Tan, Lu; Zhang, Hai-Qin; Chen, Wei-Huan; Deng, Meng-Qiu; Sha, Li-Na; Fan, Xing; Kang, Hou-Yang; Wang, Yi; Wu, Dan-Dan; Zhou, Yong-Hong
Abstract: Elymus purpuraristatus and Roegneria calcicola are perennial species of wheatgrass in Triticeae (Poaceae), treated as members of different genera on the basis of morphological characteristics. However, their genomic constitution is still unknown and their taxonomic status remains disputed. To identify their genomic constitution, we performed chromosome pairing analysis, genomic in situ hybridization and phylogenetic analyses on E. purpuraristatus and R. calcicola . The meiotic pairing results for the artificial hybrids of E. wawawaiensis (StH ) ×  E. purpuraristatus, E. purpuraristatus × Campeiostachys dahurica var. tangutorum (StYH ) and R. calcicola  ×  C. kamoji (StYH ) suggested that E. purpuraristatus and R. calcicola are allohexaploid with the St, Y and H genomes. The genomic in situ hybridization results of E. purpuraristatus and R. calcicola confirmed that they possess two sets of the H genome and two sets of the StY genome. Phylogenetic analyses suggested that Acc1 and DMC1 sequences from E. purpuraristatus and R. calcicola grouped with the St genome clade, Y genome clade and H genome clade, respectively. In summary, cytological and phylogenetic results indicated that the genome formula of E. purpuraristatus and R. calcicola is StStYYHH . According to the genomic system of classification in Triticeae, E. purpuraristatus and R. calcicola should be classified in Campeiostachys as C. purpuraristata and C. calcicola, respectively.